2017
DOI: 10.1007/s10878-017-0185-2
|View full text |Cite
|
Sign up to set email alerts
|

Computational aspects of greedy partitioning of graphs

Abstract: In this paper we consider a variant of graph partitioning consisting in partitioning the vertex set of a graph into the minimum number of sets such that each of them induces a graph in hereditary class of graphs P (the problem is also known as P-coloring). We focus on the computational complexity of several problems related too greedy partitioning. In particular, we show that given a graph G and an integer k deciding if the greedy algorithm outputs P-coloring with at least k colors is NPcomplete if P is a clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Later, Farrugia [15] has shown that if all the G i are hereditary and additive (i.e., closed under taking induced subgraphs and forming disjoint unions) then the problem is NP-hard, except the trivially polynomial case when k = 2 and both G 1 and G 2 are equal to the class of edgeless graphs. Further results in this area were obtained, e.g., by Brown [12], Alexeev et al [6], Achlioptas et al [1], or Borowiecki [10].…”
Section: Definitions and Previous Resultsmentioning
confidence: 82%
“…Later, Farrugia [15] has shown that if all the G i are hereditary and additive (i.e., closed under taking induced subgraphs and forming disjoint unions) then the problem is NP-hard, except the trivially polynomial case when k = 2 and both G 1 and G 2 are equal to the class of edgeless graphs. Further results in this area were obtained, e.g., by Brown [12], Alexeev et al [6], Achlioptas et al [1], or Borowiecki [10].…”
Section: Definitions and Previous Resultsmentioning
confidence: 82%
“…Jensen and Toft [25]). Namely, they proved that given a graph G and a positive integer k it is NP-complete to decide if Γ(G) ≥ k. Recently, their result has been extended by Borowiecki [6] who proved that for F-free coloring an analogous problem is NP-complete for every F = K p with p ≥ 3. Despite vast literature devoted to the Grundy number, we know only few graph classes for which the greedy algorithm always outputs optimal colorings (see, e.g., Borowiecki and Rautenbach [5], and Christen and Selkow [13] for more details).…”
Section: Related Research and Our Resultsmentioning
confidence: 99%
“…On the other hand, for every fixed k ≥ 2 and connected graph F, the class of graphs F-free k-colorable with the greedy algorithm can be characterized by a finite number of minimal forbidden graphs (see, Borowiecki [6]) and hence the online variant of greedy F-free k-coloring can be solved in polynomial time. Despite the fact that the structure of minimal graphs for greedy dynamic F-free coloring seems to be more involved than in the case considered in [6], we strongly believe that Problem 1.1 can also be solved in polynomial time.…”
Section: Related Research and Our Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, let L H be any g-assignment for H . Clearly, L H | H P,R is the f | V (H P,R ) -assignment, so it has property (1) or (2). If (1) holds, then to make E not monochromatic at most one colour in L H (y) is forbidden.…”
Section: Variant 1 -Proof Of Theoremmentioning
confidence: 99%